Safety, tolerability and pharmacokinetic properties of coadministered azithromycin and piperaquine in pregnant Papua New Guinean women - Moore, B.; Benjamin, J.; Auyeung, S.; Salman, S.; Yadi, G.; Griffin, S.; Page-Sharp, M.; Batty, Kevin; Siba, P.; Mueller, I.; Rogerson, S.; Davis, T. (Wiley-Blackwell Publishing Ltd., 2016)
Aims: The aim of the present study was to investigate the safety, tolerability and pharmacokinetics of coadministered azithromycin (AZI) and piperaquine (PQ) for treating malaria in pregnant Papua New Guinean women. Methods: Thirty pregnant women (median age 22 years; 16-32 weeks' gestation) were given three daily doses of 1 g AZI plus 960 mg PQ tetraphosphate with detailed monitoring/blood sampling over 42 days. Plasma AZI and PQ were assayed using liquid chromatography-mass spectrometry and high-performance liquid chromatography, respectively. Pharmacokinetic analysis was by population-based compartmental models. Results: The treatment was well tolerated. The median (interquartile range) increase in the rate-corrected electrocardiographic QT interval 4 h postdose [12 (6-26) ms0 .5] was similar to that found in previous studies of AZI given in pregnancy with other partner drugs. Six women with asymptomatic malaria cleared their parasitaemias within 72 h. Two apararasitaemic women developed late uncomplicated Plasmodium falciparum infections on Days 42 and 83. Compared with previous pregnancy studies, the area under the concentration-time curve (AUC0-8) for PQ [38818 (24354-52299) µg h l-1] was similar to published values but there was a 52% increase in relative bioavailability with each dose. The AUC0-8 for AZI [46799 (43526-49462) µg h l-1] was at least as high as reported for higher-dose regimens, suggesting saturable absorption and/or concentration-dependent tissue uptake and clearance from the central compartment. Conclusions: AZI-PQ appears to be well tolerated and safe in pregnancy. Based on the present/other data, total AZI doses higher than 3 g for the treatment and prevention of malaria may be unnecessary in pregnant women, while clearance of parasitaemia could improve the relative bioavailability of PQ.